Major Sensory Attributes and Volatile Compounds of Korean Rice Liquor (yakju) Affecting Overall Acceptance by Young Consumers - Heo, JeongAe (Foods, 2020)
The sensory characteristics and volatile compounds that affect consumers’ acceptance of rice liquors were investigated. A total of 80 consumers evaluated 12 yakju samples and descriptive analysis by 11 trained panelists was conducted. Solvent-assisted flavor evaporation-gas chromatography-mass spectrometry analysis also was conducted revealing 120 volatile compounds in the yakju samples. Sensory attributes (n = 31) except appearance attributes were used for principal component analysis (PCA). As results, fruit odor (apple, hawthorn, omija, and pineapple odor) and flower odor (chrysanthemum, pine, and peppermint odor) were placed on the positive side of PC1 whereas persimmon vinegar odor, bitter taste, alcohol flavor, stinging and coating mouthfeel were located on the negative side of PC1. The yakju samples were mainly characterized by their alcohol content and supplementary ingredients. Sensory descriptors (n = 31; except appearance attributes and p > 0.05) and volatile compounds (n = 30; p > 0.5 correlation coefficient with overall acceptance) were chosen for multiple factor analysis (MFA). The MFA correlation map showed that ethyl propanoate, ethyl-2-hydroxy-2-methylbutanoate, methyl 2-furoate, γ-butyrolactone, 4-ethoxycarbonyl-γ-butyrolactone, hawthorn odor, apple flavor, grape flavor, and sweet taste were positively correlated with young consumers’ overall acceptance. Additionally, negative correlation with overall acceptance was found in 1,3-butanediol, 2,3-butanediol, and 1,1-diethoxy-3-methylbutane.